Peningkatan Produktivitas Produksi dan Kapabilitas Pemasaran Melalui Pendampingan dan Pelatihan Pengolahan Limbah Pakaian di BUMDes Berkaho Pungpungan - Sahri Sahri; Siti Shoimah; Ita Aristia Saida (I-Com: Indonesian Community Journal, 2024)
This community service program aims to increase production productivity and marketing capabilities through assistance and training in clothing waste processing at Village-Owned Enterprises (BUMDes) Berkaho, Pungpungan Village, Kalitidu District, Bojonegoro Regency. The main problems faced by BUMDes Berkaho are the low skills and knowledge in processing clothing waste into products of economic value and limited access and ability to market these products. The training method used includes preparation, socialization, training, technology adaptation, mentoring and evaluation, and program sustainability. The results of the program show a significant improvement in clothing waste treatment skills. BUMDesa Berkaho is able to produce various handicraft products such as bags, wallets, and other accessories that have a high selling value. In addition, the trainees also showed creativity in creating new designs that are more varied and interesting. In terms of Marketing, BUMDes Berkaho was introduced to digital marketing strategies, such as the use of social media and e-commerce platforms to promote and sell products. The evaluation of the program shows that the assistance and training provided have a positive impact on increasing the income of the people of Pungpungan Village. The handicraft products produced have succeeded in attracting the interest of consumers both from inside and outside the region